Problems and Improvement Strategies of Self-Regulated Learning of Professional Degree Graduate Students from the Perspective of Integration between Industry and Education - Qian, Hangfei (Journal of Educational Research and Policies, 2024)
The integration between industry and education plays an increasingly important role in the training of professional degree graduate students, and at the same time puts forward higher requirements for the self-regulated of post-graduate learning. Based on the theory of Self-Regulated Learning, this paper investigates and analyzes the learning self-regulated of professional degree graduate students from the perspective of the integration between industry and education from two dimensions of learning motivation and learning strategy, and finds that the self-regulated learning level of professional degree graduate students is low, the self-regulated learning ability of doctoral candidates is weaker than that of master graduate students, and the self-regulated learning level of universities is different. Therefore, we should strengthen the subject consciousness of self-study, self-drive learning motivation and self-regulate learning strategies. We should improve the self-efficacy of doctoral candidates, pay attention to career development planning, and optimize the process of doctoral training. We should attach importance to the improvement of self-regulated learning ability of graduate students, strengthen the construction of academic culture, and strengthen the construction of basic resources.